2020
DOI: 10.3390/ijms21124539
|View full text |Cite
|
Sign up to set email alerts
|

HDAC8 Inhibition Reduces Lesional Iba-1+ Cell Infiltration after Spinal Cord Injury without Effects on Functional Recovery

Abstract: Pan-histone deacetylase (HDAC) inhibition with valproic acid (VPA) has beneficial effects after spinal cord injury (SCI), although with side effects. We focused on specific HDAC8 inhibition, because it is known to reduce anti-inflammatory mediators produced by macrophages (Mφ). We hypothesized that HDAC8 inhibition improves functional recovery after SCI by reducing pro-inflammatory classically activated Mφ. Specific HDAC8 inhibition with PCI-34051 reduced the numbers of perilesional Mφ as measured by histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…Entinostat is a narrow-spectrum HDAC inhibitor of class I HDAC that has been shown to possess neuroprotective functions in brain ischemia and intracerebral hemorrhage (Mota et al, 2020;Bonsack and Sukumari-Ramesh, 2021). A large number of studies have confirmed that HDACs are involved in the physiologic processes that occur following SCI (Zhang H. et al, 2018;Chen et al, 2018;Hendrix et al, 2020;Zhou et al, 2020). Recent studies have shown that HDACs tend to increase in PBMC nuclear extracts of SCI patients, including increased HDAC3 in PBMCs from SCI patients (Ma et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Entinostat is a narrow-spectrum HDAC inhibitor of class I HDAC that has been shown to possess neuroprotective functions in brain ischemia and intracerebral hemorrhage (Mota et al, 2020;Bonsack and Sukumari-Ramesh, 2021). A large number of studies have confirmed that HDACs are involved in the physiologic processes that occur following SCI (Zhang H. et al, 2018;Chen et al, 2018;Hendrix et al, 2020;Zhou et al, 2020). Recent studies have shown that HDACs tend to increase in PBMC nuclear extracts of SCI patients, including increased HDAC3 in PBMCs from SCI patients (Ma et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that HDAC1, HDAC2, and HDAC3 expressions were enhanced in the spinal cord after SCI and entinostat decreased HDAC1 and HDAC3 expressions but without affecting the HDAC2 expression. Entinostat, another class I HDAC inhibitor, has potential neuroprotective effects in brain damage (Zhang H. et al, 2018;Hendrix et al, 2020;Bonsack and Sukumari-Ramesh, 2021). Entinostat reduces NF-κB-p65 expression and nuclear accumulation as well as the neuroinflammatory response (TNF-α and IL-1β levels) in the hippocampus, which causes the improvement of postoperative cognitive dysfunction in rats (Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Collaborative Approach to Meta Analysis and Review of Animal Data From Experimental Stroke (CAMARADES) 10-item checklist were used to assess the quality and design of the studies by two independent investigators (30). The CAMARADES list includes the following: (1) Two reviewers assessed the risk of bias. Bias was marked as high or low risk, as well as "unclear" indicated that the risk of bias was unclear.…”
Section: Assessment Of Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…Spinal cord injury (SCI) is an injury to the spinal cord caused by trauma or disease, which may lead to alterations to the normal motor, sensory or autonomic function of the spinal cord ( 1 , 2 ). Traumatic SCI is a disastrous event associated with high morbidity and mortality ( 3 ).…”
Section: Introductionmentioning
confidence: 99%